The questions of literary traditional criticism in the light of Kutob Tabaqat Al-Shuara - Hussein, Nasr El Din Ibrahim Ahmed (s.n, 2012)
This study addresses the issues of the Arab Monetary old layers (Kutob Tabaqat Al-Shuara) in the books of famous poets, which are sources for the study of the traditional criticism. The layers of poets (Kutob Tabaqat Al-Shuara) contributed to books in the field of traditional literary criticism. Kutob Tabaqat Al-Shuara had many of the monetary issues, which played a prominent role in the history of literature. The cristicism since ancient times, and even age. Kutob Tabaqat Al-Shuara saved a lot of important issues from the hand of the loss, and so were the books of the early literature that looked at issues of literary criticism the old, and explained its features, and demonstrating the extent of progress since the pre-Islamic era, such as Al-Osamaa and Abn Sallam and etc